On the effectiveness of the civil regime's penalty-setting framework against insider dealing in the UK - Rustam Mirrakhimov (Journal of Economic Criminology)
This paper carries out a first-of-its-kind evaluation of the effectiveness of insider dealing policy in the UK focusing on the civil regime's penalty-setting framework against individuals. Under the assumption that there is a risk of underestimating illegal benefits from insider dealing for the purposes of a penalty determination, and due to the ambiguous punitive nature of disgorgement, the paper puts forward a novel two-step algorithm for inferring a deterrent effect from a civil financial sanction. It is found that in around half of the included cases deterrence is undermined. Hence the implementation of the policy may have been ineffective.